2005
DOI: 10.1161/01.str.0000166202.00669.d2
|View full text |Cite
|
Sign up to set email alerts
|

Steps After Stroke

Abstract: Background and Purpose-Nearly two thirds of stroke survivors have deficits impairing ambulatory recovery.Conventional mobility outcome measures such as timed walks and functional independence measure (FIM) do not quantify free-living ambulatory behavior. This study compared step activity monitoring (SAM) with established instruments to assess ambulatory recovery across the outpatient subacute stroke rehabilitation phase. Methods-We measured FIM mobility subscale, SAM-derived daily steps, Stroke Impact Scale (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 9 publications
6
64
0
Order By: Relevance
“…This study contributes to the limited findings on ambulation recovery across the subacute phase of stroke, providing further evidence that volume of activity can improve over this time 6,7 . Contrary to previous reports of a plateau in ambulation activity recovery at six months 7 , the current study demonstrated a greater improvement in ambulation activity between one and six months than between one and three months after hospital discharge.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This study contributes to the limited findings on ambulation recovery across the subacute phase of stroke, providing further evidence that volume of activity can improve over this time 6,7 . Contrary to previous reports of a plateau in ambulation activity recovery at six months 7 , the current study demonstrated a greater improvement in ambulation activity between one and six months than between one and three months after hospital discharge.…”
Section: Discussionmentioning
confidence: 64%
“…10,000 steps per day) 5 . However, observation of change in ambulation activity behaviours from the subacute (24 hours to 6-months post-stroke) to the chronic phase (> 6-months post-stroke) of stroke recovery is limited and variable 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of nondisabled individuals [19], older adults [20], and individuals with stroke [15], the SAM demonstrated greater than 95 percent accuracy and remarkably stable output during repeated testing (correlation ranges 0.84-0.98). In addition, the SAM is sensitive to changes in walking performance in individuals poststroke for up to 3 months postdischarge from acute rehabilitation, even in the absence of change in other ambulation outcome measures [21].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, conventional subacute stroke rehabilitation likely does not provide adequate exercise to reverse profound deconditioning [16]. Following completion of subacute stroke rehabilitation, patients with stroke had extremely low activity levels that further contribute to deconditioning and poor cardiovascular health as measured by microprocessor-linked step activity monitoring [23][24]. We report that community-dwelling individuals with chronic stroke take a mean of only 1,400 steps/day, with only 83 steps/day at a higher walking intensity (>30 steps/min).…”
Section: Problem Of Poststroke Deconditioningmentioning
confidence: 99%